Le Désert comme scène de l’avoir lieu : Robert Smithson et Noah Purifoy - Antonia Rigaud (Sillages Critiques)
This article looks at the works of two American artists from the second half of the 20th century : Noah Purifoy and Robert Smithson. These two sculptors question the notion of place in very similar ways, erecting their sculptures in the desert. The American desert is particularly pregnant with meaning and represents a ground for an art marked by erosion and destruction. This article discusses two iconic desert interventions : Smithson’s Spiral Jetty and Purifoy’s Outdoor Desert Art Museum, in order to bring forward the art history debates of the time, moving away from formalist criticism towards more socio-political criticism. By confronting the way these two artists conceive of sculpture in the desert, this article seeks to cross perspectives and to explore what a contextual reading of Purifoy’s work can bring to our reading of Smithson’s and, conversely, how a formalist criticism of Smithson’s art can help bring Purifoy away from the marginal space he has too long been assigned.